ОЦІНЮВАННЯ ПІДПРИЄМНИЦЬКОГО КЛІМАТУ ОБ’ЄДНАНОЇ ТЕРИТОРІАЛЬНОЇ ГРОМАДИ В КОНТЕКСТІ РОЗРОБКИ СТРАТЕГІЇ РОЗВИТКУ - Akhromkin, Ye.M.; Sieriebriak, K.I.; Belousova, L.I.; Litvinova, I.M. (Економіка та право, 2019)
The article highlights the results of entrepreneurial climate evaluation of the Lozno-Oleksandrivksa united territo rial community in the context of strategies progress and its development. The answers of enterprises and entrepreneurs on the survey concerning the entrepreneurial climate assessment of the Lozno-Oleksandrivksa village united territorial community is summarized. The enterprises and entrepreneurs of the Lozno-Oleksandrivksa united territorial community are all working practically within Ukraine. They believe that the main problems that hinder development are the following: insufficient public initiative and activity, unemployment, inadequate entrepreneurship of the community, a significant part of the older working-age population, a lack of external investment, low quality (absence) of road coverage among communities in the community. Ranking of the Lozno-Oleksandrivksa united territorial community development tasks are carried out. Priority species include agriculture / plant growing, processing of agricultural products, consulting and other intellectual services, production of building materials, agriculture / livestock. The results of cooperation evaluation level between the entrepreneurial structures of the Lozno-Oleksandrivksa united territorial community and other organizations and institutions are given. It has been established that the majority of entrepreneurial structures consider the level of cooperation with other organizations and organizations of the UTC to be satisfactory or partially satisfactory. A matrix of SWOT analysis is build, which reflects the opportunities and threats during the development of the united territorial community, its strengths and weaknesses for defining the strategic goals for the united territorial community development. REFERENCES